Images linguistiques du monde à travers des séquences figées - Sułkowska, Monika (Neophilologica, 2005)
Monika Sułkowska analyzed, on the lexical level, the problem of a linguistic image of the world, by comparing phraseological units denoting body parts in French, Italian and Polish. She came to the conclusion that although in these languages the linguistic images of the world and metaphorical meanings of expressions are similar, there are some differences between their metaphorical representations. One can often encounter expressions that differ on the aspect of an employed body part e.g. French avoir la tete sur les epaules and Polish mieć głowę na karku. Most of the differences in the organization of such idiomatic expressions are connected with the names of upper limbs (arm, shoulder, hand, palm), lower limbs (leg, foot) and names like nape or armpit The opposition appears usually between French and Italian on one side, and Polish on the other. The observed differences in representation can be explained by the sernic analysis and by the prototypical cognitive structures.